Regulation effect of seed priming on sowing rate of direct seeding of rice under salt stress - Zhang, Yicheng; Sultan, Haider; Shah, Asad; Mu, Yixue; Li, Yusheng; Li, Lin; Huang, Zheng; Song, Shaokun; Tao, Ye; Zhou, Zhenxiang; Nie, Lixiao (Frontiers in Plant Science, 2025)
Direct seeding of rice (DSR) is a widely used method for its labor- and cost-saving advantages. However, the global intensification of soil salinization presents a significant challenge to food security. Increasing sowing rates is a common practice to enhance germination under salt stress, although it leads to higher seed costs. Recently, seed priming has emerged as an effective technique to improve seedling emergence under abiotic stress, but the regulation of seed priming treatment on the sowing rate of DSR under saline soil conditions has rarely been reported. Therefore, field experiments were conducted at two salinity levels of 1.5‰ (1.5 g kg−1) (T2) and 3.0‰ (3 g kg−1) (T3) and under one non-saline condition (0‰) (T1). The control (P1) consisted of non-primed seeds, while priming treatments included 160 mg L−¹ ascorbic acid (P2), γ-aminobutyric acid (P3), and 200 mg L−¹ zinc oxide nanoparticles (P4); three sowing rates were applied: 90 (S1), 150 (S2), and 240 seeds m−2 (S3). Our results demonstrated that under T1–T3, the germination rate, α-amylase activity, and soluble sugar and protein contents were significantly increased after priming treatments. The contents of reactive oxygen species (i.e., O2− and H2O2) and malondialdehyde (MDA) were decreased, while the activities of enzymatic antioxidants (i.e., superoxide dismutase, peroxidase, and catalase) and the K+/Na+ ratio of rice were significantly increased after the above seed priming treatments. Under T1–T3, the grain yield increased by 13.39%–36.94% after priming treatments, primarily due to enhanced seed germination, which boosted panicle number per unit area. Among P2–P4 treatments, P4 treatment consistently resulted in the highest yield increase (26.96%–36.94%) compared to P1, outperforming P2 and P3 under T1–T3. Furthermore, under T1–T3, the grain yield with priming treatment at 90 seeds m−2 was equivalent to that obtained without priming treatment at 240 seeds m−2. The potential mechanisms by which priming treatments enhance rice salt tolerance include increased levels of osmoregulatory substances and elevated activities of antioxidant enzymes, which collectively support improved seed germination. Therefore, to optimize the economic benefits of DSR when the salt concentration is below 3‰, the sowing rate could be reduced to 90 seeds m−2 using ZnO-nanoparticle priming treatment.